Pengungkapan Sustainability Report dan Firm Value - I Wayan Kartana; Desi Tri Ira Santi; I Made Wianto Putra; Putu Gede Wisnu Permana Kawisana; Ida Ayu Sri Meitri (Jurnal Ekonomi Akuntansi dan Manajemen, 2023)
The primary purpose of having a sustainability report is to enhance the confidence of the public in the company, ultimately leading to an increase in the company's worth. Firm Value refers to how investors perceive the company and is a significant factor they consider when making investment choices. The aim of this study is to analyze how the disclosure of Sustainability Reports affects the valuation of companies that are listed on the Sri-Kehati Stock Index. The sample selection was carried out using the purposive sampling method, so as to obtain a sample of 7 companies with an observation period of 5 years (2017-2021). This study employs quantitative data analysis, specifically using secondary data obtained from sustainability reports and annual reports accessed through the respective company websites. The research utilizes multiple linear regression as the chosen technique. The findings of this study suggest that there is no notable impact on the value of Sri-Kehati Stock Index Listed Companies based on the disclosure of sustainability reports, economic disclosures, environmental disclosures, and social disclosures. These results have theoretical implications, as they challenge the ability of stakeholder theory to explain the findings, while behavioral theory may provide a more suitable explanation. Furthermore, this research has practical implications for both issuers and the government, indicating that the disclosure of sustainability reports does not contribute to an increase in firm value. Keywords: Disclosure of Sustainability Report, Firm Value